2021
DOI: 10.3390/healthcare9070843
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intervention Improves Nutrition Outcomes in Stomach and Colon Cancer Patients Receiving Chemotherapy: Finding from a Quasi-Experiment in Vietnam

Abstract: Background: Evidence on the effects of nutritional interventions on gastrointestinal cancer patients receiving chemotherapy is not well documented. This study aims to assess the effects of nutritional intervention in patients diagnosed with stomach and colon cancer receiving chemotherapy in Vietnam. Methods: A quasi-experiment with intervention and control groups for pre- and post-intervention was carried out in cancer patients receiving chemotherapy in a university hospital in Vietnam. Patients in the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 36 publications
0
23
0
2
Order By: Relevance
“…Another study involving mice revealed that administering quercetin (another flavonoid in soybean) supplements significantly decreased body weight loss, thus attenuating the progression of cancer cachexia (Velázquez et al, 2014). Similarly, cancer patients who received oral nutrition supplements in a quasi-experimental study benefited positively by experiencing an increase in their weight and muscle mass (Huong et al, 2021). supported by some evidence in literature, which has shown that cancer patients who received nutritional therapy with high-protein intake resulted in an improvement of their QoL and physical functioning and performance (Chen et al, 2022;Isenring, 2013;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study involving mice revealed that administering quercetin (another flavonoid in soybean) supplements significantly decreased body weight loss, thus attenuating the progression of cancer cachexia (Velázquez et al, 2014). Similarly, cancer patients who received oral nutrition supplements in a quasi-experimental study benefited positively by experiencing an increase in their weight and muscle mass (Huong et al, 2021). supported by some evidence in literature, which has shown that cancer patients who received nutritional therapy with high-protein intake resulted in an improvement of their QoL and physical functioning and performance (Chen et al, 2022;Isenring, 2013;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study involving mice revealed that administering quercetin (another flavonoid in soybean) supplements significantly decreased body weight loss, thus attenuating the progression of cancer cachexia (Velázquez et al., 2014). Similarly, cancer patients who received oral nutrition supplements in a quasi‐experimental study benefited positively by experiencing an increase in their weight and muscle mass (Huong et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is effective in minimizing selection bias to control for confounding variables and to rule out chance [19], [20]. There are also some previous studies that assessed the impact of nutrition interventions using this method [21], [22]. Since the sampling was not random, the difference in differences method (DiD) [20] was used to evaluate the effectiveness of the intervention for nutritional indicators in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hasilnya didapat pasien di kelompok kontrol dalam 2 bulan mengalami peningkatan berat badan 1.4 ± 2.6 kg and 0.4 ± 2.3 kg. Pada kelompok intervensi menunjukkan peningkatan ukuran massa otot 1.2 ± 4.1 cm (Huong et al, 2021).…”
Section: Pembahasanunclassified
“…Banyak efek samping dari pengobatan ini diantaranya nafsu makan menurun, dispepsia, kelelahan, konstipasi, diare, disfagia, perubahan sensitivitas terhadap suhu makanan, xerostomia, anemia, dan rasa cepat kenyang. Faktor-faktor tersebut berhubungan dengan penurunan asupan makanan, penurunan penyerapan nutrisi, perubahan komposisi tubuh, dan akibatnya dapat menyebabkan malnutrisi dan cachexia (Huong et al, 2021).…”
unclassified